Viking families and farms - Hopkins, Andrea (New York : PowerKids Press, 2002)
Provides information about the lives of Vikings, discussing how and where they lived, farming activities, family units, slavery, the work of men and women, colonizing, and festivities.
Includes index.
5.7
3-6
Keywords: Northmen -- Social life and customs -- Juvenile literature; Vikings -- Social life and customs -- Juvenile literature; Farm life -- Scandinavia -- History -- Juvenile literature; Scandinavia -- Social life and customs -- Juvenile literature; Northmen -- Social life and customs; Vikings -- Social life and customs; Farm life -- Scandinavia -- History; Scandinavia -- Social life and customs; Vikings -- Social life and customs; Farm life -- Scandinavia -- History; Scandinavia -- Social life and customs